Seeding system and density for winter Urochloa ruziziensis intercropped with sorghum between soybean crops - Buffara, Marco Antônio; Silva, Alessandro Guerra da; Teixeira, Itamar Rosa; Costa, Kátia Aparecida de Pinho; Simon, Gustavo André; Goulart, Maria Mirmes Paiva (Comunicata Scientiae, 2018)
The intercrop of grain sorghum with Urochloa ruziziensis allows the production of grains and biomass in the winter. Thus, the objective of this study was to identify the more adequate seeding system and seed density for Urochloa ruziziensis intercropped with sorghum between soybean crops to obtain high grain and biomass yields with these species and evaluate the performance of the subsequent soybean crop. The experiments were carried out in the winter of 2015 and in the 2015-2016 crop season in Rio Verde GO, and Santa Helena de Goiás GO, Brazil. The treatments consisted of three seeding systems (in-row, inter-row, and broadcast), and five seed densities (2, 4, 6, 8, and 10 viable seeds m-2) of U. ruziziensis intercropped with sorghum, using monocultures of sorghum and U. ruziziensis as controls. The seeding density of 8 viable seeds m-2 of U. ruziziensis using in-row seeding, and up to 10 viable seeds m-2 using inter-row, and broadcast seedings do not decrease sorghum grain yield. Increasing seeding density of U. ruziziensis increases its dry matter yield, and the total dry matter yield when intercropped with sorghum. The intercrop of sorghum with U. ruziziensis increases the soil plant coverage. The dry matter of the intercrop of sorghum with U. ruziziensis does not affect soybean grain yield.